Effects of the Whole-Body Vibration Exercise on Sleep Disorders, Body Temperature, Body Composition, Tone, and Clinical Parameters in a Child with Down Syndrome Who Underwent Total Atrioventricular Septal Defect Surgery: A Case-Report - Luiza Torres-Nunes; Patrícia Prado da Costa-Borges; Laisa Liane Paineiras-Domingos; José Alexandre Bachur; Ana Carolina Coelho-Oliveira; Danúbia da Cunha de Sá-Caputo; Mario Bernardo-Filho (MDPI AG, 2023)
Background: The health and developmental issues of people with Down syndrome (DS) are complex and are associated with many medical, psychological, and social problems from childhood through into adulthood. DS children have an increased risk of multiorgan comorbidities, including congenital heart disease. Atrioventricular septal defect (AVSD) is a congenital heart malformation that often occurs in DS people. Aim: Physical activity and exercise are recommended for patients with cardiovascular disease and are considered to be the gold standard of cardiac rehabilitation. Whole-body vibration exercise (WBVE) is considered a form of exercises. The aim of this case report is to show the effects of WBVE on sleep disturbances, body temperature, body composition, tone, and clinical parameters in a child with DS with corrected total AVSD. The subject is a 10-year-old girl, with free-type DS, who underwent surgery to correct a total AVSD at 6 months. She underwent periodic cardiological monitoring and was released to perform any type of physical exercise, including WBVE. WBVE improved sleep quality and body composition. Conclusion: WBVE leads to physiological effects that benefit the DS child.